User-Generated Content in Increasing Consumer Engagement: Opportunities and Challenges - Gunawan Gunawan (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2024)
This study aims to analyze the role of User-Generated Content (UGC) in increasing consumer engagement as well as to identify the opportunities and challenges faced by companies in utilizing it as a digital marketing strategy. UGC refers to content created and shared by consumers, such as product reviews, photos, videos, or testimonials, which has now become an important element in building relationships between brands and consumers. This study uses a descriptive method with observations, interviews, and document analysis related to the research. The results show that User-Generated Content (UGC) is effective in increasing consumer engagement with brands through authentic and participatory content. UGC can expand market reach and build stronger trust compared to traditional marketing content. However, the success of using UGC is also influenced by challenges such as fake reviews, the need for proper content moderation, and protection of users’ personal data. With good moderation strategies and attention to data security, UGC can become a powerful tool to enhance consumer loyalty and interaction in the digital ecosystem.